Struktur Komunitas Echinodermata pada Habitat Padang Lamun di Pantai Kawasan Puntondo Kabupaten Takalar Sulawesi Selatan - Marliana (Jurnal Riset Diwa Bahari (JRDB), 2023)
This study aims to determine the species composition and community structure of Echinodermata and their relationship with seagrass cover and oceanographic parameters in the Puntondo Coastal Area. The study was carried out from October to November 2021. Seagrass observations and samples of Echinodermata used the random sampling method at three stations representing natural zones, near settlements, and ecotourism. The observations used the line transect method by stretching the transect line perpendicular to the sea for 100 meters with a distance between transects of 50 meters. The results showed that the number of echinoderm species composition identified was 15 species from 4 classes. The community structure of Echinodermata at three stations indicates a moderate level of diversity, a high uniformity index indicates an even distribution and a dominance index indicates that no species dominates. The percentage area of seagrass cover at three station points in the Puntondo Coastal Area belongs to the medium cover category. The condition of the waters on the coast of the Puntondo area at three station points meets the quality standard requirements for marine biota. The relationship between dominance, seagrass cover, and pH showed a positive relationship while abundance, diversity, uniformity, temperature, salinity, brightness, and currents showed a negative relationship.